Active labour market policy presented by Measure No. 1.2 “Perspectives for youth” undertook within Sectoral Operational Programme Human Resources Development 2004-2006 - Natalli, Krzysztof (Publishing House of the Wrocław University of Economics, 2009)
The situation in the labour market is one of the most important factors which enable to evaluate the economy condition and unemployment constituting one of the most serious problems of contemporary market economies. Although this phenomenon has been attracting attention of economists since the 18th century, there are still problems with creating its universal and accurate definition. Most definitions from the literature define only general identification criteria without giving detailed principles of their interpretation. Unemployment most often is defined as a lack of income generating jobs among people in the economically productive age who are able and ready to work and are actively looking for a job [Kwiatkowski 2002, pp. 20-21]. It is only when calculating the scale of unemploy-ment in practice that it is necessary to define what we mean by: an economically productive age, ability or readiness to work or searching a job. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 334-343